Search for extraterrestrial life: habitability of the planetary system Gliese 667C - Pacheco, José Antônio de Freitas (Cadernos de Astronomia, 2022)
In this short paper are discussed the habitability conditions of exoplanets and, in particular, those affecting directly the presence of liquid water at the surface. The climate of planets depends strongly on the presence of an atmosphere, on the greenhouse gases and on the carbon-silicate cycle, which guarantees the climate stability over geological timescales. These ideas are applied to the planetary system present in Gliese 667C constituted by five “super-Earths”. The present analysis suggests that only Gliese 667C c has climate conditions adequate for the emergence of life.
Keywords: astrobiology; Gliese 667C; exoplanets; habitability; life emergency